A novel framework of MOPSO-GDM in recognition of Alzheimer's EEG-based functional network - Wang, Ruofan; Wang, Haodong; Shi, Lianshuan; Han, Chunxiao; He, Qiguang; Che, Yanqiu; Luo, Li (Frontiers in Aging Neuroscience, 2023)
Most patients with Alzheimer's disease (AD) have an insidious onset and frequently atypical clinical symptoms, which are considered a normal consequence of aging, making it difficult to diagnose AD medically. But then again, accurate diagnosis is critical to prevent degeneration and provide early treatment for AD patients. This study aims to establish a novel EEG-based classification framework with deep learning methods for AD recognition. First, considering the network interactions in different frequency bands (δ, θ, α, β and γ), multiplex networks are reconstructed by the phase synchronization index (PSI) method, and fourteen topology features are extracted subsequently, forming a high-dimensional feature vector. However, in feature combination, not all features can provide effective information for recognition. Moreover, combining features by manual selection is time-consuming and laborious. Thus, a feature selection optimization algorithm called MOPSO-GDM was proposed by combining multi-objective particle swarm optimization (MOPSO) algorithm with Gaussian differential mutation (GDM) algorithm. In addition to considering the classification error rates of support vector machine, Bayesian, and discriminant analysis classifiers, our algorithm also considers distance measure as an optimization objective. Finally, this method proposed achieves an excellent classification error rate of 0.0531 (5.31%) with the feature vector size of 8, by a ten-fold cross-validation strategy. These findings show that our framework can adaptively combine the best brain network features to explore network synchronization, functional interactions, and characterize brain functional abnormalities, which can improve the recognition efficiency of diseases. While improving the classification accuracy of application algorithms, we aim to expand our understanding of the brain function of patients with neurological disorders through the analysis of brain networks.